Supervision Implementation to Improve Education Quality in Integrated PN Merangin Vocational School (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
Education is said to be of quality if the education has an increase and results in the Human Resources themselves. The purpose of this research is to examine how the implementation of supervision in educational institutions at the Integrated PN Vocational High School level, precisely in the village of Ampun Baru, West Pamenang District, Merangi Regency, The province of Jambi. the role of supervision in educational institutions at the Integrated Merangin PN Vocational High School is very important, because it can have an impact on an institution's educational quality. This research method uses descriptive qualitative. data collection is done by observation, in-depth interviews and documentation. The learning process carried out by the instructor, as well as the teacher's lack of expertise and understanding, have a large effect on the high and bad quality of education.Therefore the researcher can formulate the problem that how is the effort to implement educational supervision carried out at educational institutions at the Merangin Integrated PN SMK. because at this SMK institution has a vocational in Animal Husbandry. This supervision is carried out by supervisors at the high school level.